Evaluation Of Bakauheni River Vessel Capacity - A Agus Tjahjono; Driaskoro Budi Sidharta; Indriana Indriana (IWJ : Inland Waterways Journal, 2021)
The Bakauheni Ferry Terminal is a ferry port that connects Sumatra and Java Island, which has a crossing distance of 15 miles. The Bakauheni - Merak route has 71 (seventy one) ships which operate for a regular boat travel time of 108 minutes while the executive ship travel time is 90 minutes. The average passenger productivity on the Bakauheni-Merak route is 477 passengers and the vehicle is 184 vehicles. The large productivity of passengers and vehicles on the Bakauheni-Merak route causes the ship's carrying capacity to be incompatible with the ship's particular ship. It is known that the Jatra 3 ship in the particular ship particular has a allowable capacity of 115 vehicles. However, based on observations it is known that the carrying capacity of more than 115 vehicles, The method of analyzing the carrying capacity on the ship uses the analysis of the daily load factor calculation. The primary data used is in the form of productivity data under normal conditions (January-March 2020) and during the covid-19 pandemic (April-May 2020) The results of the analysis show that the average daily load factor under normal conditions is 105% and during the Covid-19 pandemic it is 88%.